Design methods and practices for research of project management - Pasian, Beverly; Turner, Rodney (Routledge, 2024)
Design Methods and Practices for Research of Project Management is the most comprehensive guide on how to do research on and in project management. Project management as a discipline has experienced near-exponential growth in its application across the business and not-for-profit sectors. This second edition of the authoritative reference book offers a substantial update on the first edition with over 60% new content and so provides both practitioner and student researchers with a fully up-to-date and complete guide to research practice on project management. In Design Methods and Practices for Research of Project Management, Beverly Pasian and Rodney Turner have brought together 26 original chapters from many of the leading international thinkers in project management research. The collection looks at each step in the research stages, including research strategy, management, methodology (quantitative and qualitative), and techniques as well as how to share and publish research findings. The chapters offer an international perspective with examples from a wide range of project management applications; engineering, construction, megaprojects, high-risk environments, and social transformation. Each chapter includes tips and exercises for the research student, as well as a complete set of further references. The book is the go-to text for practitioners undertaking research in companies, and also doctoral and master's students and their supervisors who are involved in research projects in and for universities.